Associations Between Core Temperature Disorders and Outcomes of Pediatric Intensive Care Unit Patients. - Kiekkas, Panagiotis; Kourtis, Grigorios; Feizidou, Paraskevi; Igoumenidis, Michael; Almpani, Eleni; Tzenalis, Anastasios (American Journal of Critical Care, 2023)
Background: The few studies of associations between fever and outcomes in pediatric intensive care unit (PICU) patients have conflicting findings. Associations between hypothermia and patient outcomes have not been studied. Objective: To investigate the incidence and characteristics of fever and hypothermia and their associations with adverse outcomes among PICU patients. Methods: Patients consecutively admitted to 2 PICUs in a 2-year period were prospectively studied. Core temperature was mainly measured by rectal or axillary thermometry. Fever and hypothermia were defined as core temperatures of greater than 38.0 °C and less than 36.0 °C, respectively. Prolonged mechanical ventilation, prolonged PICU stay, and PICU mortality were the adverse patient outcomes studied. Associations between patient outcomes and core temperature disorders were evaluated with univariate comparisons and multivariate analyses. Results: Of 545 patients enrolled, fever occurred in 299 (54.9%) and hypothermia occurred in 161 (29.5%). Both temperature disorders were independently associated with prolonged mechanical ventilation and prolonged PICU stay (P <.001) but not with PICU mortality. Late onset of fever (P <.001) and hypothermia (P =.009) were independently associated with prolonged mechanical ventilation, fever magnitude and duration (both P <.001) were independently associated with prolonged PICU stay, and fever magnitude (P <.001) and infectious cause of hypothermia (P=.01) were independently associated with higher PICU mortality. Conclusions: These findings provide evidence that the manifestation and characteristics of fever and hypothermia are independent predictors of adverse outcomes in PICU patients.